Patients with chronic diseases: Is sexual health brought up by general practitioners during appointments? A web-based study - Manninen Sanna-Mari; Polo-Kantola Päivi; Vahlberg Tero; Kero Katja (Elsevier Ireland Ltd, 2022)
Objectives
Many chronic diseases and their medications may induce sexual problems. This study aimed to evaluate whether general practitioners (GPs) raise sexual health issues during appointments with patients who have chronic diseases.
Study design
A web-based questionnaire was distributed to a random sample of 1,000 GPs in Finland.
Main outcome measures
The study aim was to determine GPs’ self-reported inquiry into sexual problems with patients who have chronic diseases and GPs’ awareness of medications inducing sexual problems.
Results
Only 16.2% of the GPs inquired about sexual health issues, typically during appointments dealing with reproductive organs. A majority (66.9%) considered sexual problems to be side-effects of medications, but only 17.9% followed up about them. Compared to male GPs, female GPs were more likely to inquire about gynecologic patients’ sexual issues (OR 1.77, 95% CI 1.05–2.99), but less likely to ask about them with urologic (OR 0.56, 95% CI 0.35–0.91) and neurologic patients (OR 0.35, 95% CI 0.17–0.72). The GPs aged 40–49 and 50–65 were more likely than those aged 27–39 to inquire about sexual health issues among patients with cardiovascular (OR 2.87, 95% CI 1.11–7.44, OR 2.89, 95% CI 1.16–7.19) and neurologic (OR 4.63, 95% CI 1.45–14.82, OR 5.68, 95% CI 1.87–17.23) diseases.
Conclusions
GPs seldom inquire about sexual problems with patients who have chronic diseases or after prescribing medications for these conditions, which may lead to underdiagnosis and undertreatment of sexual problems.